A new criterion for defining the failure of a fractured rock mass slope based on the strength reduction method. Issue 1 (1st January 2020) - Wei, Yuan; Hanhua, Tan; Jiandong, Niu; Shu, Peng; Yanyu, Xue; Wei, Wang; Xiaoyun, Sun
Abstract: In this study, a stability analysis approach for fractured rock mass slopes is proposed by combining the strength reduction method ( SRM ) with the undirected graph theory ( UGT ). First, the original shear strength parameters of all the fractures are divided by the same reduction coefficient to generate new shear strength parameters, which are used for numerical simulations of the fractured rock mass slope. Second, the connectivity of the failure fractures is analyzed with a self-developed code, which is developed based on UGT . If no fracture clusters are fully connected from the top of the slope to the toe or free face of the slope, the slope is considered to be stable, and the reduction coefficient is incremented. The above calculation procedures are repeated until there is exactly right a fracture cluster is fully connected (i.e. slope is leaded to critical state). The reduction coefficient that coincides with the critical state is considered as the safety factor of the slope, and the fractured rock mass encompassed by the connected failure fractures is regarded as the unstable part of the slope. Finally, the proposed method is applied to analyze the stability and the potential failure range of a steep slope to verify its validity.